The public purse : a study in Canadian democracy - Ward, Norman, 1918-1990 (Canadian government series, 1951)
The book demonstrates how erratic the Commons' record has been, ranging from the good to the very bad, and while recent developments in the House appearing promising, they do not yet offer convincing evidence of a permanent change towards effective scrutiny by it of expenditure by the executive.